1986
DOI: 10.2165/00003088-198611030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interactions of Commonly Used Anticancer Drugs

Abstract: With the use of combination chemotherapy as well as a wide range of symptomatic therapies (e.g. analgesics and antiemetics) for the treatment of patients with cancer, the field of oncology practises polypharmacy to an extreme degree. The risk for a drug interaction under these conditions is high, and the pharmacological characteristics of the anti-cancer drugs, such as steep dose-response curves, low therapeutic indices and severe toxicities, suggest that even small changes in the pharmacokinetic profile of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Theoretically, salicylate herbs (e.g., cramp bark, willow, wintergreen) could interact with methotrexate or similar cytotoxic drugs, decrease the excretion of those drugs, and induce increased plasma levels of those drugs. 28 The current study revealed that 84% of Japanese oncologists were concerned about interactions between anticancer drugs and CAM products and that 91.8% experienced concurrent use of anticancer drugs with CAM products. However, our present knowledge of interactions is incomplete, especially regarding anticancer drugs, and more research is needed urgently.…”
Section: Discussionmentioning
confidence: 78%
“…Theoretically, salicylate herbs (e.g., cramp bark, willow, wintergreen) could interact with methotrexate or similar cytotoxic drugs, decrease the excretion of those drugs, and induce increased plasma levels of those drugs. 28 The current study revealed that 84% of Japanese oncologists were concerned about interactions between anticancer drugs and CAM products and that 91.8% experienced concurrent use of anticancer drugs with CAM products. However, our present knowledge of interactions is incomplete, especially regarding anticancer drugs, and more research is needed urgently.…”
Section: Discussionmentioning
confidence: 78%
“…At Toffoli/Errante/Corona/Vaccher/ Bertola/Robieux/Aita/Sorio/Tirelli/ Boiocchi present, the biochemical bases of the modulation of C max and T max of ZDV by chemotherapy are not clearly understood. The antineoplastic drugs could determine some effects on the gastrointestinal mucosa by affecting gastric motility, which could interfere with the kinetics of ZDV absorption, as demonstrated for other drugs [20,27]. It must be considered that Ruhnke et al [28] reported a decrease in ZDV peak after food intake as a consequence of inhibition of gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the rare cases where the patient does develop acute renal failure from treatment, the serum levels of MTX will persist until renal function improves. Certain drug interactions may also lead to renal dysfunction and place the patient at excessive risk of toxicity [3,11,12].…”
Section: Discussionmentioning
confidence: 99%